2011
DOI: 10.1021/ja2037029
|View full text |Cite
|
Sign up to set email alerts
|

An M2L4 Molecular Capsule with an Anthracene Shell: Encapsulation of Large Guests up to 1 nm

Abstract: A new M(2)L(4) molecular capsule with an aromatic shell was prepared using two Pd(II) ions and four bisanthracene ligands. The self-assembled capsule possesses a cavity with a diameter of ~1 nm that can encapsulate medium-sized spherical and planar molecules as well as a very large molecule (C(60)) in quantitative yields. The encapsulated guests are fully segregated and shielded from the external environment by the large anthracene panels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
171
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 304 publications
(179 citation statements)
references
References 31 publications
5
171
1
2
Order By: Relevance
“…Supramolecular nanocapsule 1 provides a spherical cavity protected by eight anthracene panels (Fig. 1b) [24][25][26] . The capsule assembles from two Pd(II) ions and four bent bispyridine ligands 2 with two embedded anthracene rings in a quantitative yield and encapsulates neutral guest molecules with the size up to 1 nm, in which the guests are shaded from the outside by the closed polyaromatic shell.…”
mentioning
confidence: 99%
“…Supramolecular nanocapsule 1 provides a spherical cavity protected by eight anthracene panels (Fig. 1b) [24][25][26] . The capsule assembles from two Pd(II) ions and four bent bispyridine ligands 2 with two embedded anthracene rings in a quantitative yield and encapsulates neutral guest molecules with the size up to 1 nm, in which the guests are shaded from the outside by the closed polyaromatic shell.…”
mentioning
confidence: 99%
“…2a) with two embedded anthracene panels to design molecular tube 1. The rigidly bent conformation of 2b facilitates the formation of supramolecular assemblies such as (i) capsular structures through noncovalent, coordinative transition-metal linkages [18][19][20][21] and (ii) bowlshaped structures through covalent methylene linkages 22,23 . For the preparation of the tubular structure, we employed Zincke reaction 24,25 to form two phenyl-pyridyl bonds on 1 without using a transition-metal catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H NMR spectra of 2a and 3 show complicated signals for the pyridyl and phenyl rings (Fig. 2b,c) due to the presence of the atropisomers arising from hindered rotation around the anthryl-aryl bonds 18 . In contrast, the 1 H NMR spectrum of tube 1 revealed eight clearly resolved aromatic signals (H g-j and H G-J ) assignable to the N-phenylpyridinium moieties between 7.86 and 9.86 p.p.m.…”
Section: Resultsmentioning
confidence: 99%
“…These stable hostguest structures were clearly established by NMR, UVvis, and ESI-TOF MS analyses. Kishi and Yoshizawa et al reported that anthracene-shelled M 2 L 4 capsule 4 displays a wide range of host capability toward neutral organic molecules, 12,17 in sharp contrast to previous M 2 L 4 cages with wire-like frameworks. 11 For instance, when a slight excess of hydrophobic [2.2]paracyclophane was suspended in an aqueous solution (2:1 methanol/water) of capsule 4, a 1:1 hostguest complex was obtained quantitatively (Figure 8a).…”
Section: Synthesis Of Polyaromatic-shelled Cages and Capsulesmentioning
confidence: 96%
“…12 Anthraceneshelled M 2 L 4 capsule 4 was quantitatively formed from Pd(II) ions and bent bis(pyridyl) ligands bearing two anthracene panels connected by a m-phenylene spacer ( Figure 5a). Two or three methoxyethoxy groups on the phenylene ring serve to increase the solubility of the capsule in aqueous solutions.…”
Section: Synthesis Of Polyaromatic-shelled Cages and Capsulesmentioning
confidence: 99%